2018
DOI: 10.1371/journal.pone.0200813
|View full text |Cite
|
Sign up to set email alerts
|

Associations between pneumonia and residential distance to livestock farms over a five-year period in a large population-based study

Abstract: In a recent study of electronic health records (EHR) of general practitioners in a livestock-dense area in The Netherlands in 2009, associations were found between residential distance to poultry farms and the occurrence of community-acquired pneumonia (CAP). In addition, in a recent cross-sectional study in 2494 adults in 2014/2015 an association between CAP and proximity to goat farms was observed. Here, we extended the 2009 EHR analyses across a wider period of time (2009–2013), a wider set of health effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
45
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 15 publications
7
45
2
Order By: Relevance
“…Nevertheless, contrary to the study of van Dijk et al [15], we found no significant differences in the prevalence of chronic bronchitis/bronchiectasis for the years 2014-2016, despite the generally higher rates in the livestock dense areas. The current results are also consistent with analyses using individual estimates of exposure to different livestock types in relation to primary care-registered data, showing an increased prevalence of pneumonia with higher livestock density [9,14,16]. This was also the case for studies including self-reported outcome assessments [29,30], despite that prevalence estimates based on self-reported questionnaires can deviate from those extracted from medical records [31,32].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, contrary to the study of van Dijk et al [15], we found no significant differences in the prevalence of chronic bronchitis/bronchiectasis for the years 2014-2016, despite the generally higher rates in the livestock dense areas. The current results are also consistent with analyses using individual estimates of exposure to different livestock types in relation to primary care-registered data, showing an increased prevalence of pneumonia with higher livestock density [9,14,16]. This was also the case for studies including self-reported outcome assessments [29,30], despite that prevalence estimates based on self-reported questionnaires can deviate from those extracted from medical records [31,32].…”
Section: Discussionsupporting
confidence: 87%
“…More specifically, the prevalence of primary care-registered pneumonia and other lower respiratory tract infections, as well as chronic bronchitis, was found to be consistently higher in livestock dense areas compared to areas with low livestock density [14,15]; a higher prevalence of nonrespiratory conditions such as atopic eczema was also observed in both young children and adults [14]. Analyses in the same area including individual estimates of livestock exposure in relation to primary care-registered data have also demonstrated that living near goat and/or poultry farms is a risk factor for pneumonia [9,14,16] and also Q-fever [9,14]. Other findings also indicate a possible impact of livestock exposure on the health status of patients with compromised respiratory health; these showed increased respiratory symptoms and more exacerbations among chronic obstructive pulmonary disease (COPD) patients residing in livestock dense areas [17,18], while livestock exposure was also associated with respiratory symptoms in patients with overlapping diagnoses of asthma and COPD [19].These previous findings reflect the need for regular health-monitoring in areas with high livestock density.…”
mentioning
confidence: 95%
“…In two studies investigating cases of pneumonia in relation to proximity to goat farms, a significantly elevated incidence of the disease was also found near poultry farms [9, 12]. A similar association between pneumonia and proximity to poultry was recently reported in Pennsylvania, USA [16], yet in two other studies in the Netherlands, those associations were not significant and positive in only some of the analyses [5, 11].…”
Section: Introductionsupporting
confidence: 62%
“…Conversely, persons that have COPD and live close to livestock farms were found to have increased COPD exacerbation [7, 8]. Recently, an increased risk of pneumonia was observed in the Netherlands among residents living close to goat and poultry farms [912].…”
Section: Introductionmentioning
confidence: 99%
“…Inquiries about potential animal exposures are important, but explicit exposure is often absent. Since Coxiella burnetii transmission often occurs via the air (up to kilometers from infected animal), the diagnosis of chronic Q fever with vascular involvement should be considered in any case of aortitis/mycotic aneurysm and periaortic abscess of unknown etiology [911].…”
Section: Discussionmentioning
confidence: 99%